Guest

Questions 18 complete sollution required for the question above .

Questions 18 complete sollution required for the question above . 

Question Image
Grade:

1 Answers

Arun
25758 Points
4 years ago
Dear Pushkar
 
 
take it as
a2+b2+c2-ab-bc-ca=0
Multiply both sides with 2, we get
2( a2 + b2 + c2 – ab – bc – ca) = 0
2a2 + 2b2 + 2c2 – 2ab – 2bc – 2ca = 0
(a2 – 2ab + b2) + (b2 – 2bc + c2) + (c– 2ca + a2) = 0
(a –b)2 + (b – c)2 + (c – a)2 = 0
Since the sum of square is zero then each term should be zero
(a –b)2 = 0,  (b – c)2 = 0, (c – a)2 = 0
(a –b) = 0,  (b – c) = 0, (c – a) = 0
a = b,  b = c, c = a
a = b = c.
therefore c+a/b=2
 
Regards
Arun

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free